And Yet He is a Monist: Comments on James Kreines, Reason in the World. Issue 1 (17th October 2016) - Knappik, Franz
Abstract: I critically discuss Kreines's arguments against readings on which Hegel holds some version of metaphysical monism. In section 1, I address Kreines's claim that Hegel's revised version of Kant's argument in the Transcendental Dialectic implies a rejection of metaphysical monism. I argue both that the argument that Kreines ascribes to Hegel does not itself rule out monism, and that there are serious exegetical problems with the way Kreines understands Hegel's diagnosis of the antinomies and his critique of the metaphysics of the understanding. In section 2, I discuss additional reasons that Kreines gives for seeing Hegel as rejecting metaphysical monism. In particular, I argue that Hegel is much more optimistic about the intelligibility of nature than Kreines thinks: to a substantial degree, the basic structure of nature, including the laws of mechanics, is open to explanations that are ultimately based on a monistic principle.